Composition of The essential oils of Tanacetum densum (Lab.) schultz Bip. subsp. amani and T. densum (Lab.) schultz Bip. subsp. laxum (Asteraceae) from Turkey - Bagci, Eyup (Chemical Publishing Co., 2009)
The aerial parts of Tanacetum densum subsp. amani and T. densum subsp. laxum were hydrodistilled to produce the oils with yields of 0.30 % (v/w) and 0.15 % (v/w), respectively. The oils were analyzed by GC and GC/MS. Seventy three and seventy components were identified representing 92.2 and 80.6 % of the oils, respectively. The main compounds of T. densum subsp. amani were a-pinene (3.0 %), 1,8-cineole (14.7 %), borneol (31.3 %) and endoborneol (21.0 %). Whereas a-pinene (5.0 %). (+)-epi-bicyclosesquiphellandrene (31.4 %), a-cadinol (7.0 %), 1 -heptadecanol (5.6 %) and eicosane (3.2 %) were the major constituents in T. densum subsp. laxum. Distribution of the predominate compounds in essential oil were discussed among the Tanacetum genus patterns.
Keywords: 8-Cineole; Borneol; Essential oil; Tanacetum; Tanacetum densum